2008
DOI: 10.1091/mbc.e07-03-0261
|View full text |Cite
|
Sign up to set email alerts
|

Identification of an Axonal Kinesin-3 Motor for Fast Anterograde Vesicle Transport that Facilitates Retrograde Transport of Neuropeptides

Abstract: A screen for genes required in Drosophila eye development identified an UNC-104/Kif1 related kinesin-3 microtubule motor. Analysis of mutants suggested that Drosophila Unc-104 has neuronal functions that are distinct from those of the classic anterograde axonal motor, kinesin-1. In particular, unc-104 mutations did not cause the distal paralysis and focal axonal swellings characteristic of kinesin-1 (Khc) mutations. However, like Khc mutations, unc-104 mutations caused motoneuron terminal atrophy. The distribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

32
194
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(233 citation statements)
references
References 58 publications
(85 reference statements)
32
194
1
Order By: Relevance
“…Microtubules and actin filaments significantly contribute to directional mobility in neuronal axons (Barkus et al, 2008). NELL2 associates with microtubule-actin crosslinking factor 1 (Macf1) in retinal ganglion cells (Munemasa et al, 2012).…”
Section: Microtubule-dependent Transport Of Nell2-egfp Vesiclesmentioning
confidence: 99%
“…Microtubules and actin filaments significantly contribute to directional mobility in neuronal axons (Barkus et al, 2008). NELL2 associates with microtubule-actin crosslinking factor 1 (Macf1) in retinal ganglion cells (Munemasa et al, 2012).…”
Section: Microtubule-dependent Transport Of Nell2-egfp Vesiclesmentioning
confidence: 99%
“…In this way, θ 's for all positive anisotropies of u accumulate positive as well as negative votes from the neighboring points that have non-negligible weights in the decay function according to (4). In the end, the receiver point u appears to be a ridge if the sum of positive votes exceeds that of the negative votes.…”
Section: Refining the Kymograph Using Orientation Votingmentioning
confidence: 99%
“…For instance, the transport of membranous organelles along axons is of vital interest in studies of neurodegenerative diseases, especially Huntington's and Alzheimer's [1][2][3][4]. For example, Ferrer et al in [3] found that a key role of huntingtin (HTT) protein is to regulate transport of secretory granules containing Brain-derived Neurotrophic Factor (BDNF), and that loss of this function may contribute to pathogenesis in Huntington's disease.…”
Section: Introductionmentioning
confidence: 99%
“…Based on Galbraith et al [29], diffusivity of NF polymers is estimated to be 0.43 µm/s 2 while diffusivity of tubulin oligomers is estimated to be 8.6 µm/s 2 .…”
Section: Perturbation Solutionmentioning
confidence: 99%
“…Their long processes, axons, can reach up one meter in length, and occupy up to 99% of neuron's volume; this makes transport of organelles in axons extremely challenging [1,2]. Despite these challenges, axonal transport is crucial to axon survival and functioning; this is because axons contain little synthetic machinery; new organelles, synthesized in the cell body, must be continuously transported toward distal portions of the axon while old and used components must be returned to the cell body for reprocessing.…”
Section: Introductionmentioning
confidence: 99%